The Impact of Financial Technology Adoption on the Sustainability of Microenterprises in Indonesia: The Mediating Role of Financial Inclusion - Mekar Meilisa Amalia (West Science Journal Economic and Entrepreneurship, 2026)
The rapid development of financial technology (fintech) has transformed financial access and operational practices among micro businesses, particularly in emerging economies such as Indonesia. This study aims to examine the impact of financial technology implementation on the sustainability of micro businesses, with financial inclusion serving as a mediating variable. A quantitative research approach was employed using data collected from 150 micro business actors through a structured questionnaire measured on a Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3) to evaluate both measurement and structural models. The results indicate that fintech implementation significantly enhances financial inclusion and directly improves business sustainability. Financial inclusion also has a significant positive effect on sustainability and partially mediates the relationship between fintech adoption and sustainable business performance. These findings suggest that digital financial innovation contributes to micro business resilience when supported by inclusive financial access. The study provides theoretical contributions to digital finance and sustainable entrepreneurship literature while offering practical implications for policymakers and fintech providers in promoting inclusive digital ecosystems for micro-enterprise development in Indonesia.